Strukturdan Asosiasi Komunitas Tumbuhan Bawahdi Resort Cikaniki, Taman Nasional Gunung Halimun Salak - Rizmoon Nurul Zulkarnaen (Universitas Hasanuddin, 2017)
A study on structure and association of ground cover plants commnunity was conducted in Cikiniki Resort, Gunung Halimun Salak National Park, West Java. The aimed of this study was to determine the structure and degree of association of ground cover plant that dominates with others ground cover plants. Plot observation using purposive sampling method. The sampling location was divided into two observation sites near the water source and away from the water source. We developed 20 plots with measure on 2 x 2 m2. The data obtained are frequency, density, dominance, Importance Value Index (INP), Distribution Index and Diversity Index Type. The relationship between abiotic factor and vegetation association was analyzed using Chi-Square analysis. The results showed that the dominant type was Schismatoglottis calyptrata (Roxb.) Zoll. & Moritzi (INP: 41.67%), Homalomena cordata Schott (INP: 16.87%), Cyrtandra populifolia Miq. (INP: 12.27%), Psychotria viridiflora Reinw. Ex Blume (INP: 11.79%) and Amischotolype mollissima (Blume) Hassk. (INP: 10,77%). Based on the calculation of chi-square (X2) associations S.calyptrata with other dominant species have low values of 0.26 (H. cordata), 0.25 (C. populifolia), 0.275 (P. viridiflora) and has no association with A. mollissima.